Backchannelling In Film Dialogue: A Pragmatic Analysis of Tenggelamnya Kapal Van Der Wijck - Rani Rakasiwi; Masriani; Marlina Br. Tampubolon; Ricki Asi Erwindo Siahaan (Journal of Applied Linguistics, 2026)
Backchannelling has an important role in making film conversations sound natural and emotionally meaningful. This study discusses the use of backchannelling expressions in the film Tenggelamnya Kapal Van Der Wijck. Backchannelling refers to short responses produced by listeners, such as “uh-huh,” “yeah,” “right,” and “I see,” which indicate attention, understanding, agreement, emotional reaction, and active participation during interaction (Yngve, 1970). This research aims to identify the types of backchannelling expressions found in the film, explain their communicative functions, and examine the frequency of their use. This study applies a qualitative descriptive approach. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldana (2014), which consists of data condensation, data display, and conclusion drawing and verification. The findings show that the characters in the film frequently employ four main categories of backchannelling, namely minimal responses, agreement tokens, emotional responses, and continuers (McCarthy, 2003; Ward, 2006). Among these categories, agreement tokens appear most frequently, followed by minimal responses, emotional responses, and continuers. The analysis also indicates that backchannelling functions as a conversational strategy to express attentiveness, comprehension, empathy, emotional engagement, solidarity, and encouragement for speakers to continue their utterances. Furthermore, this study contributes to the fields of pragmatics, conversation analysis, and media discourse by emphasizing that backchannelling is not merely a linguistic feature, but also an interactional strategy that supports effective communication and strengthens interpersonal relationships in conversation Keywords : Backchannelling; Pragmatics; Conversation Analysis, Film Discourse; Listener Response